Gastric Reflux. Issue 2 (March 2015) - Schallom, Marilyn; Orr, James A.; Metheny, Norma; Kirby, John; Pierce, Janet
<x xml:space="preserve">Abstract</x> Background: Gastric reflux leading to pulmonary aspiration is a frequent event in mechanically ventilated, gastric-fed patients, which can lead to ventilator-associated complications and pneumonia. Objectives: The objectives of this study were to determine the association between gastric reflux and aspiration using the presence of pepsin in oral or tracheal secretions as a marker of reflux or aspiration and to determine the association between the pH (range, 0-14) and the presence of pepsin in oral secretions. Methods: A descriptive correlational study was conducted in mechanically ventilated surgical or medical patients receiving gastric tube feedings. Oral secretions were suctioned hourly and tracheal secretions every 2 to 3 hours for 12-hour periods over 1 to 2 days in 15 patients. Results: There were 142 paired samples of oral tracheal secretions. A majority of samples (60%) had the same results, with 32% both pepsin-positive and 27% both pepsin-negative. The range of pH measurements was 4 to 8, with a mean of 6.3 ± 0.05. Ninety oral specimens had a pH of 4 to 6. Forty-seven of the oral specimens with pH measures between 4 and 6 (52%) were pepsin-positive. The correlation of pH percent pepsin-positive oral secretions was not significant. Conclusion: Aspiration events were more frequent than reflux events. Measurement of actual pepsin concentration to detect new reflux and aspiration events is recommended in future studies. Bedside pH measures of oral secretions are not a valid marker of gastric reflux.